Effect of substituent polarity, bulk, and substitution site toward enhancing gas permeation in dibromohexafluorobisphenol-A based polyarylates - Ishole, Yogesh S.; Karadkar, Prasad R.; Kharul, Ulhas K. (Journal of Polymer Science Part B-Polymer Physics, 2007)
The gas permeation properties of polyarylates were tuned by varying nature and site of substituents present on both of its monomers, viz., bisphenol and dicarboxylic acid. The phenyl rings of hexafluorobisphenol-A were substituted in asymmetric manner by polar bromine to obtain dibromohexafluorobisphenol-A. This bisphenol was polymerized with equimolar mixture of iso- and terephthalic acid (base case), bromo- and nitroterephthalic acid (polar group substituted acids), 4,4'-hexafluoroisopropylidene bis(benzoic acid), and t-butyl isophthalic acid (bulky group containing acids). Physical properties and gas permeation properties of these polyarylates were investigated to assess combined effects of asymmetric nature of bisphenol substitution, polar nature of substituent bromine, hexafluoroisopropylidene group present at the bridge position of bisphenol, and substituent present on the acid moiety. The combination of these substituent types led these polyarylates to lie near Robeson upper bound. The gas sorption analysis and estimation of diffusivity in these polyarylates shed a light on observed variations in gas permeation properties by attempted structural variations. (c) 2007 Wiley Periodicals, Inc.
Keywords: asymmetric substitution; Diffusion; Gas permeation; gas sorption; polyarylates; selectivity; structure-property relations